- 734
- 0
for this equation, y=vx, it's the same as v=y/x
however, if i differenate the 1st equation, dy/dx=v+x*dv/dx
and if i differenate the 2nd equation, dv/dx=(1/x)*dy/dx + [-1/(x^2)]y
but both differenated equations don't seem the same...
does somebody know where my calculuations went wrong?
however, if i differenate the 1st equation, dy/dx=v+x*dv/dx
and if i differenate the 2nd equation, dv/dx=(1/x)*dy/dx + [-1/(x^2)]y
but both differenated equations don't seem the same...
does somebody know where my calculuations went wrong?